MUDANÇA TECNOLÓGICA E REORDENAÇÃO SOCIAL DA VELHICE - Neves, Delma Pessanha (Cadernos de Ciência & Tecnologia, 1996)
O artigo apresenta uma análise do paradoxo da colocação em prática de um intenso processo de incorporação de mudança tecnológica na região açucareira de Campos (RJ) que, longe de reafirmar os pressupostos da modernização da agricultura, estimulou a reprodução simples de pequenas unidades agrícolas, muitas delas administradas por produtores idosos, orientados pela manutenção de sua posição de chefe autônomo da unidade familiar. A reprodução desta posição se ancora na rejeição de novas técnicas agrícolas, constrangimento a partir do qual é possível assegurar a gestão da reposição dos pressupostos da produção. TECHNOLOGICAL CHANGE AND SOCIAL REORGANIZATION IN OLD AGE ABSTRACT The article presents an analysis of the paradox of putting into practice an intense process of incorporation of technological change in the sugar producing region of Campos county, Rio de Janeiro State, which, far from reaffirming the assumed modernization of agriculture, stimulated the simple reproduction of small agricultural units, many of them administered by elderly producers, oriented to the maintenance of their position of autonomous head of the family unit. The reproduction of this position is anchored in the rejection of new agricultural techniques, a restraint starting from which it is possible to assure the management of the re-establishment of the presupposition of the production.